Takut, Bertaut, and Runtuh: Analizing the Authenticity of Autobiographical Lyrics and Their Relation With Youth Reception (Jurnal Seni Musik, 2023)
Previous studies showed that love has become an eternal theme in pop music. But since the early 2000s, new themes with negative sentiments such as pain, despair, fear, and sadness have emerged in pop music. Along with this phenomenon, recent pop music offers poetic lyrics instead of cliché lyrics. What makes them more interesting is, some of the lyrics are autobiographical. This study aims to analyze the originality of autobiographical lyrics and their relation to young listeners’ reception. The researchers use three songs as the research object: Takut by Idgitaf, Bertaut by Nadin Amizah, and Runtuh by Feby Putri and Fiersa Besari. This qualitative research uses the lyrics of those songs and questionnaire results as its data. The questionnaire respondents are young listeners between 18 and 30 years old who live in different villages and cities in Indonesia with various social economic and educational backgrounds. The collected data are analyzed using Fraith and Hoggarts’ thoughts. Analysis of the works of Idgitaf, Nadin Amizah, Feby Putri, and Fiersa Besari shows that all of them have distinct and unique songwriting skills. They also show consistency in choosing the theme song, including the three songs used as research objects. Out of 64 respondents, 56.3% claim that knowing a song is an autobiographical work does not change their opinion and feelings toward the song. However, the result of the questionnaire shows that young listeners feel connected to song lyrics that represent their feelings.